Rotational excitation of bridges supported on pile groups in soft or liquefiable soil deposits. (15th July 2015) - Sextos, Anastasios G.; Mylonakis, George E.; Mylona, Elli-Konstantina V.
Abstract: This paper investigates the seismic response of reinforced concrete bridges founded on pile groups in soft or liquefiable soil deposits under simultaneous translational and rotational earthquake excitation. The pile cap rotational excitation results from pile bending under vertically propagating seismic S-waves. The response of the pile cap (in terms of displacement and rotation) defines the Foundation Input Motion (F.I.M.) computed through kinematic interaction analysis. The resulting superstructure demand due to the coupled translational and rotational excitation is compared to the demand developed due to translational only F.I.M. The results confirm earlier observations regarding the impact of pile bending on rigid body rotations of bridges founded with cast-in-drilled hole single piles. It is also shown that the excitation mechanism of pile groups in soft soils is non-uniform along the pile length, thus exciting higher modes of vibration and inducing out-of-phase translational and rotational response of the pile cap.